The Psychometric Properties of the Norwegian version of The Children’s Communication Checklist - Second Edition (CCC-2) - Reindal, Lise; Brøndbo, Per Håkan; Jozefiak, Thomas (PsykTestBarn, 2022)
Description: The Children’s Communication Checklist-Second Edition (CCC-2; Bishop, 2003) assesses spoken and pragmatic language in children aged 4:0-16:11 years. The Norwegian and international owner is Pearson Assessment. The checklist was translated to Norwegian by Wenche Andersen Helland and Lillian Hollund-Møllerhaug, with assistance from clinical expertise, and published in 2011. The checklist consists of 70 items grouped into 10 subscales, that are further combined into composite scores: The General Communication Composite (GCC; in Norwegian GKI) and The Social Interaction Deviance Composite (SIDC; in Norwegian IASI). The CCC-2 results provide information on structural and pragmatic language skills, as well as social aspects of communication that are commonly affected in children with autism spectrum disorder (ASD). Interpretation of CCC-2 scores and profiles requires expertise in the language area. Literature search: Of 196 Scandinavian publications 11 Norwegian articles fulfilled the inclusion criteria. Four of these were publications related to the Norwegian standardization. The samples mainly comprised school-aged children, with subsamples of children in treatment or evaluated by school psychology services, speech and language therapists, or specialist health services. Two of the 11 included studies were based on relatively small samples with specific syndromes. Psychometrics: The Norwegian and British percentile distribution of GCC scores show a similar but not equivalent pattern. GCC scores corresponding to the 10th percentile were higher in the Norwegian sample. Norwegian studies further support the reliability, construct validity and criterion validity. Conclusion: The psychometric properties of the Norwegian version of the CCC-2 are promising but have not yet been sufficiently examined. The construct validity is supported by several reports of expected score differences between clinical groups and groups of typically developing children. Internal consistency of the subscales is found to be consistent with the British version. There is a dearth of Scandinavian studies on factor structure, criterion validity, and interrater reliability. Furthermore, the Norwegian norm base is limited. Based on the available documentation, CCC-2 seems to be a valid instrument for identifying children with possible language impairments, and children who should be examined more closely for ASD. However, further research to clarify the appropriate GCC cut-off for identification of language impairments in Scandinavian samples is warranted. Interpretation of CCC-2 profiles in a clinical setting should be done with caution, and by qualified professionals only.